2001
DOI: 10.1080/14015430152928357
|View full text |Cite
|
Sign up to set email alerts
|

Tongue-to-palate contact patterns and variability of four English consonants in an /i/ vowel environment

Abstract: Log Phon Vocol 2001; 26: 165-178 Minimal data exist describing tongue-to-palate contact patterns and their variability in normal speakers of English. Consequently, the aims of the present study were to examine, using a comprehensive pro le of data analysis, tongue-topalate contact patterns and their variability in a group of ten normal speakers of English using the Reading Electropalatography3 (EPG3) system. Each speaker produced ten repetitions of the target words tea, leap, sea, and key following the carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
21
0
1

Year Published

2006
2006
2009
2009

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 15 publications
7
21
0
1
Order By: Relevance
“…Therefore, as anticipated, examination of the ORFs of contact revealed similar tongue-palate contact patterns across the three groups. Furthermore, these tongue-palate contact patterns were consistent with previous descriptions of EPG patterns in normal speakers Hardcastle, Morgan Barry, & Clark, 1987;Dagenais, Lorendo, & McCutcheon, 1994;Hardcastle, & Gibbon, 1997;Murdoch, Gardiner, & Theodoros, 2000;McAuliffe et al, 2001). However, closer analysis of the ORF for /li/ by the participant group with PD revealed inconsistent closure patterns at row two on the palate.…”
Section: Lateral Approximant /L/supporting
confidence: 89%
See 3 more Smart Citations
“…Therefore, as anticipated, examination of the ORFs of contact revealed similar tongue-palate contact patterns across the three groups. Furthermore, these tongue-palate contact patterns were consistent with previous descriptions of EPG patterns in normal speakers Hardcastle, Morgan Barry, & Clark, 1987;Dagenais, Lorendo, & McCutcheon, 1994;Hardcastle, & Gibbon, 1997;Murdoch, Gardiner, & Theodoros, 2000;McAuliffe et al, 2001). However, closer analysis of the ORF for /li/ by the participant group with PD revealed inconsistent closure patterns at row two on the palate.…”
Section: Lateral Approximant /L/supporting
confidence: 89%
“…These consisted of indices and measures used previously by a variety of authors. Specifically, these measures included: amount of tongue-palate contact, most anterior row contacted, number of rows with complete closure, length of closure in the midline, location of the point of maximum constriction, groove width and the modified Centre of Gravity Index (mCOG) (Hardcastle, Gibbon, & Jones, 1991;Hardcastle, Gibbon, & Nicolaidis, 1991;Jones, & Hardcastle, 1995;McAuliffe et al, 2001;Goozee, Murdoch, & Theodoros, 2003). The mCOG differs slightly from the commonly used Centre of Gravity (COG) index Jones, & Hardcastle, 1995) as progressively higher weighting is allocated to contact that Tongue-palate contact patterns in PD occurs in the more posterior regions of the palate (Scott, & Goozee, 2002).…”
Section: Spatial Palatal Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Placement for /n/ may be identified by perceptual analysis as like /t/ and /d/, but there may be subtle differences in its articulation that can only be detected with an instrumental technique such as EPG, which measures details of the tongue's contact against the palate. A number of previous EPG studies of normal adult speakers' productions of alveolar stops have shown that /t/, /d/ and /n/ do in fact have similar "horseshoe" shaped configurations (Dagenais, Lorendo and McCutcheon, 1994;Goozée, Murdoch and Theodoros, 1999;Hardcastle and Gibbon, 1997;McLeod and Roberts, 2005;McLeod, 2006;McAuliffe, Ward and Murdoch, 2001;Stone and Lundberg, 1994). EPG studies show that normal speakers (adults and children) produce this horseshoe configuration by a combination of lateral bracing and an upward movement of the tongue tip/blade to the alveolar ridge (Dagenais and Critz-Crosby, 1991;Fletcher, 1989).…”
Section: Introductionmentioning
confidence: 99%